Tyrosine 67 Phosphorylation Controls Respiration and Limits the Apoptotic Functions of Cytochrome c - Junmei Wan; Paul T. Morse; Matthew P. Zurek; Alice A. Turner; Asmita Vaishnav; Arthur R. Salomon; Brian F. P. Edwards; Tasnim Arroum; Maik Hüttemann (Cells)
Cytochrome c (Cytc) is a multifunctional protein, essential for respiration and intrinsic apoptosis. Post-translational modifications of Cytc have been linked to physiological and pathophysiologic conditions, including cancer. Cytc tyrosine 67 (Y67) is a conserved residue that is important to the structure and function of Cytc. We here report the phosphorylation of Y67 of Cytc purified from bovine heart mapped by mass spectrometry. We characterized the functional effects of Y67 Cytc modification using in vitro and cell culture models. Y67 was mutated to the phosphomimetic glutamate (Y67E) and to phenylalanyl (Y67F) as a control. The phosphomimetic Y67E Cytc inhibited cytochrome c oxidase (COX) activity, redirecting energy metabolism toward glycolysis, and decreased the pro-apoptotic capabilities of Cytc. The phosphomimetic Y67E Cytc showed a significantly impaired rate of superoxide scavenging and a reduced rate of oxidation by hydrogen peroxide, suggesting a lower ability to transfer electrons and scavenge reactive oxygen species (ROS). Phosphomimetic Y67E replacement led to an almost complete loss of cardiolipin peroxidase activity, pointing to a central role of Y67 for this catalytic function of Cytc. In intact cells, phosphomimetic replacement leads to a reduction in cell respiration, mitochondrial membrane potential, and ROS levels. We propose that Y67 phosphorylation is cardioprotective and promotes cell survival.